A Historical critique of eight major current trends in language teaching circumstances of their emergence - Lopez, Love Lester A. (College of Arts and Letters, University of the Philippines Diliman, 1995)
This thesis discusses the historical development of eight major current trends in language teaching namely Grammar Translation Method, Direct Method, Audio-Lingual Method, Silent Way, Suggestopedia, Community Language Learning, Total Physical Response and Communicative teaching Method. In addition, it aims to answer the question: Why is a particular method replaced by a new method? The emergence of new methodologies is a result of three circumstances: (1) The previous methodology's failure to meet the needs of the language learners; (2) The new research findings on the theories of the nature of language and language learning brought about by Linguistics, Behavioral Psychology, and Sociology; and (3) The changing views on language education brought about by the changing political, social and economic climates of the period.